Pendataan dan Pemetaan Potensi Sumberdaya Alam Serta Pengembangan Produk Unggulan Desa - Agus Hikmat; Yoga Dwi Syahputra; Viyata Pratiwi Risky; Ghiyats Fawwaz Fadhlullah; Devi Aldian Pratama; Rani Assyifa; Ditha Silva Mutiawati (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
The development of the agricultural sector at the village level needs to be supported by the availability of data on the potential of the village area, especially the existing natural resources and superior community products that can be developed in the future. The purpose of this activity is to make maps or tools in analyzing the potential of the Parakan Village and Karangtengah Village areas and developing superior product processing. Activities carried out through interviews with village officials and field visits. All activities were successfully carried out while still implementing health protocols. The results of this activity succeeded in recording and making maps of the potential of natural resources in the village area and the development of superior processed products for the people of Parakan Village and Karangtengah Village. The map of the potential for natural resources and superior processed products can help the village development in the future to improve community welfare. Key words: potential map, superior products, village communities